Perdamaian Antara Pelaku dan Korban Bullying: Studi Deskriptif Resolusi Perdamaian Antara Pelaku dan Korban Bullying pada SMA Negeri di Pusat Kota Surabaya - Nadhif, Nadhif Fahar Ananda (Paradigma, 2025)
This study discusses bullying among high school students in the city of Surabaya, this study seeks to provide solutions regarding the pattern of peace between perpetrators and victims of bullying and the role of people around in reducing bullying that occurs among students. This research uses theories from Johan Galtung and Lewis A. Coser in which discusses conflict and peace. This research uses qualitative methods. The location of this research was conducted at SMAN 1, 2, 5, 9, SMAN 6, and SMAN 21 Surabaya. The results of research that have been conducted at SMA Negeri 2, 9 and 21 Surabaya show that there is bullying behavior that occurs in schools. Perpetrators and victims of bullying that occurred in downtown Surabaya based on the results of research conducted by researchers contained the peace pattern of Johan Galtung who defined that non-violent creative conflict can be transformed as a form of peace. Peace patterns can be done with the following steps namely Prevention, Intervention and Handling, Victim Support, Education and Awareness, Collaboration.